1982
DOI: 10.1016/s0022-5347(17)52879-7
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Urothelium in Analgesic-Associated Nephropathy—A Valuable Diagnostic Aid

Abstract: A brownish discoloration of the bladder mucosa on cystoscopy and the histological findings in a bladder biopsy specimen of submucosal vascular basement membrane thickening, pigment or chronic inflammatory changes in the absence of infection were present in various combinations in all our patients with analgesic-associated nephropathy. None of these findings was present in a control group of patients with other established causes of renal function impairment. More objective diagnostic aids may lead to a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Fourie et al . reported that experimental analgesic abuse results in prominent renal vascular proliferation and our histopathological finding of prominent capillary blood vessels in the lamina propria of the renal pelvis is consistent with this report 5 . Levitt et al .…”
supporting
confidence: 92%
“…Fourie et al . reported that experimental analgesic abuse results in prominent renal vascular proliferation and our histopathological finding of prominent capillary blood vessels in the lamina propria of the renal pelvis is consistent with this report 5 . Levitt et al .…”
supporting
confidence: 92%